Uji Kuat (Kuat Tekan) Paving Block Hasil Konversi Sampah Plastik - Khosiin Khosiin; Nurlia Latpah (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This research aims to determine the compressive strength of paving blocks produced from plastic waste through a comparison with paving blocks made from a mixture of plastic and sand, as well as factory-produced paving blocks used for the UIN Fatmawati Sukarno Bengkulu campus courtyard. The research is conducted using an experimental method, starting with the manufacturing of plastic-based paving blocks and followed by strength testing in the civil engineering laboratory of the University of Bengkulu. The results of the research show that the compressive strength of factory-produced paving blocks made from sand and cement averages 5.9 MPa, while the compressive strength of paving blocks made from a mixture of plastic and sand averages 1.32 MPa, and the average compressive strength of paving blocks is 2.23 MPa. In conclusion, the compressive strength of paving blocks made from pure plastic or a mixture of plastic and sand is still below the SNI 03-0691-1996 standard due to the brittle nature of plastic. Keywords: Conversion, Plastic, Paving Block